Ibnu Hazm: (384h / 994m - 456h / 1064m) Epistemologi dalam Pendidikan - Sahputra, Very Nanda; Farma, Muhammad Daud (Al Mabhats : Jurnal Penelitian Sosial Agama, 2023)
Abstract: Ibn Hazm is a prominent Andalusian Islamic thinker with expertise in philosophy, law, education, and economics. Ibn Hazm's ideas and concepts have evolved and are still relevant today. As a result, this study focuses on Ibn Hazm's biography and the impact of his ideas on the field of education. This is a qualitative study using the literature technique. The study's findings reveal the structure of Ibn Hazm's ideas in the following areas. First, emphasizing the importance of writing skills in out-of-school education can be a useful strategy for preventing illiteracy. Second, in the education system, attention to the degree of formal education is given in stages based on the development of students' intelligence. Third, once kids recognize letters, they learn to write and read at the same time. Ibn Hazm's epistemology is primarily concerned with the development of humans who are illiterate and possess realistic and reasonable thinking. The study has implications for home education patterns, demonstrating that children's intellectual growth can be attained through a collaboration of roles between schools and families, particularly in learning to write and read. Abstrak: Ibnu Hazm dikenal sebagai ulama besar Islam Andalusi yang ahli di bidang filsafat, hukum, pendidikan dan ekonomi. Dalam perkembangannya, gagasan dan pemikiran Ibnu Hazm sangat relevan diterapkan hingga pada saat ini. Oleh sebab itu penelitian ini secara spesifik mengkaji biografi Ibnu Hazm dan kontribusi pemikirannya terhadap dunia pendidikan. Penelitian ini berjenis kualitatif dengan teknik kepustakaan. Hasil penelitian mengungkap konstruk pemikiran Ibnu Hazm dalam beberapa poin berikut (1) penekanan terhadap pentingnya kemampuan menulis dalam pendidikan luar sekolah dapat menjadi solusi efektif untuk menghindari buta huruf. (2) Dalam sistem pendidikan, perhatian terhadap jenjang pendidikan formal dilakukan secara bertahap sesuai perkembangan kecerdasan peserta didik. (3) Konsep pembelajaran menulis dan membaca dilakukan secara bersamaan setelah mereka mengenal huruf. Secara esensial epistemologi Ibn Hazm berorientasi terhadap penciptaan manusia yang terbebas dari buta huruf dan memiliki pemahaman realistik dan rasional. Penelitian berimplikasi terhadap pola pendidikan keluarga bahwa perkembangan intelektual anak dapat dicapai melalui sinergitas peran antara sekolah dan keluarga khususnya dalam pembelajaran menulis dan membaca.